Students' Mathematical Procedural Fluency Based on Self-regulated learning - Samuel Zebua; Edwin Waruwu (Journal of Innovation and Research in Primary Education, 2022)
Mathematical procedural fluency is an important aspect and must be mastered by students, whose mathematical skills are built on conceptual understanding, strategic competence, adaptive reasoning, and problem-solving. Procedural skills are also related to attitude aspects such as self-regulated learning. Therefore, this study aims to analyze mathematical procedural fluency based on students' self-regulated learning. The research method used is descriptive qualitative. The subjects in this study involved 10 6th grade students at SDN 075061 Balodano. The data analysis technique was carried out descriptively through analysis text. The description of students' self-regulated learning and its relation to mathematical procedural fluency was also analyzed descriptively through a graphical display of data. The results showed that the general description of students' mathematical procedural fluency was still relatively low. However, in general, students showed a positive attitude towards self-regulated learning. Overall, the results of this study indicate a relationship between mathematical procedural fluency and self-regulated learning.